Philosophy 167: Class 3 - Part 3 - Towards Disentangling the Various Observed Motions: Astronomia Nova, Real Planetary Movement, and the First and Second Inequalities. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Introduces Kepler's arguments on how to analyze the motions of the planets. Gives some history on his book came to be published. Describes details about retrograde motion and the implications for describing orbits.; Opening line: "In the introduction you'll be reading next week, this is Astronomia Nova."; Duration: 6:29 minutes.; Segment: Class 3, Part 3.